(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2018)
In this issue of the journal, there are two articles on bacterial sensitivity to antibiotics. An internet literature survey using Google as the search engine confirmed well documented antibiotic resistance among common bacteria. For example, resistance to penicillins occurs in approximately 80 % of all strains of Staphylococcus aureus. Surprisingly, Streptococcus pyogenes (Group A Streptococcus) are very susceptible to penicillins. Multi-drug resistance is also common. The first documented case of bacterial multi drug resistance involved a strain of the dysentery bacillus isolated in Japan in 1953. It was found to be resistant to tetracycline, chloramphenicol, streptomycin and a sulphonamide. Today many other bacteria often referred to as ‘superbugs’ are known to be resistant to multiple drugs. There are several risk factors that contribute to the development of multiple drug resistance. Top on the list is the indiscriminate use of antibiotics by both health professionals and non-professionals.